Conditional differences in mean reaction time explain effects of response congruency, but not accuracy, on posterior medial frontal cortex activity. - Joshua eCarp; Kamin eKim; Stephan F Taylor; Kate Dimond Fitzgerald; Daniel H Weissman (Frontiers in Human Neuroscience, 2010)
According to the conflict-monitoring model of cognitive control, the posterior medial frontal cortex (pMFC) plays an important role in detecting conflict between competing motor responses. Consistent with this view, pMFC activity is greater in high-conflict trials (e.g., incongruent trials and errors) than in low-conflict trials (e.g., congruent trials and correct responses) of distractor interference tasks. However, in both low- and high-conflict trials, pMFC activity increases linearly with RT. Thus, heightened pMFC activity in high-conflict trials may simply reflect the fact that mean RT is longer in high-conflict than in low-conflict trials. To investigate this hypothesis, we reanalyzed data from a previously published fMRI study in which participants performed an event-related version of the multi-source interference task (MSIT). Critically, after controlling for conditional differences in mean RT, effects of response congruency on pMFC activity were eliminated; in contrast, effects of response accuracy on pMFC activity remained robust. These findings indicate that effects of response congruency on pMFC activity may index any of several processes whose recruitment increases with time on task (e.g., sustained attention). However, effects of response accuracy reflect processes unique to error trials. We conclude that effects of response accuracy on pMFC activity provide stronger support for the conflict-monitoring model than effects of response congruency.